2019
DOI: 10.1007/s00259-019-04452-y
|View full text |Cite
|
Sign up to set email alerts
|

PET/MRI versus PET/CT in oncology: a prospective single-center study of 330 examinations focusing on implications for patient management and cost considerations

Abstract: PurposePET/MRI has recently been introduced into clinical practice. We prospectively investigated the clinical impact of PET/MRI compared with PET/CT, in a mixed population of cancer patients, and performed an economic evaluation of PET/MRI.MethodsCancer patients referred for routine staging or follow-up by PET/CT underwent consecutive PET/CT and PET/MRI, using single applications of [18F]FDG, [68Ga]Ga-DOTANOC, or [18F]FDOPA, depending on tumor histology. PET/MRI and PET/CT were rated separately, and lesions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(54 citation statements)
references
References 34 publications
2
48
0
4
Order By: Relevance
“…PET/MRI, a multimodal and multiparametric technique, may provide more quantitative information than PET/CT [ 58 ]. Even though the per-examination cost of 18F-FDG PET/MRI is approximately 50% higher, the possibility of a one-stop-shop solution for, for example, node-positive breast cancer patients could not only reduce costs in initial staging but could also reduce the burden on the patient [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…PET/MRI, a multimodal and multiparametric technique, may provide more quantitative information than PET/CT [ 58 ]. Even though the per-examination cost of 18F-FDG PET/MRI is approximately 50% higher, the possibility of a one-stop-shop solution for, for example, node-positive breast cancer patients could not only reduce costs in initial staging but could also reduce the burden on the patient [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hybrid PET/MR has been introduced into the clinical application setting since 2011. Studies on the feasibility and potential applications of PET/MR imaging have been reported soon after that, and oncology was one of the hot topic (4)(5)(6)(7)(8). Because multiparametric PET/MR imaging can provide many biomarkers of the studied diseases non-invasively, it was widely used in oncological research, especially for the tumor diagnosis, treatment planning, surveillance, and follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…[1525] With recent advances in imaging, different groups have studied the predictive value of whole body CT, positron-emission CT (PET-CT), and PET-MRI in their respective settings; they recommend initial use of these techniques to increase the yield of cancer detection. [262728] Overall, PET-CT appears to be a reasonable choice depending on the availability and cost constraints, especially in patients presenting with solitary lesions. [29]…”
Section: Discussionmentioning
confidence: 99%